Niezwykłe historie z udziałem dzieci w apoftegmatach Anastazego z Synaju - Drzyżdżyk, Szymon; Gilski, Marek (Vox Patrum, 2024)
The article is devoted to the problem of the child in the apophthegmata of Anastasius of Sinai. They present a wide panorama of life and behavior of children and youth in the context of a specific era and place. The structure of the article is determined by five contexts in which the subjective role of the child is shown as a victim, debtor, dissenter, experiencing spiritual revelations and experiencing possession and healing. The analyses made it possible to formulate specific conclusions, the most significant of which concern Anastasius’ belief that faith is such a great value that it justifies depriving even one’s children of their lives in order to protect them from apostasy, and that the teenager is capable of an independent act of faith for which he is willing to suffer martyrdom. Moreover, in the mind of the monk from Sinai, childhood is a period when one can experience extraordinary religious experiences. This applies to both "private revelations" and healings. This article also poses an important question that can be an inspiration for further research, namely what happened in the Church that in the era of the desert fathers and the strong development of monastic life in which references to the Old Testament practices - the sacrifices of Abraham and Jephthah - were so strongly voiced, and there was no reference to Jesus and his relationship with children? This sets a completely new horizon in their treatment.